2018
DOI: 10.1016/j.jaci.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab for Treatment of Asthma: Post-Approval Academic Practice Experience

Abstract: RATIONALE: Mepolizumab has been approved for treatment in severe eosinophilic asthma. However, there are no post-approval practice-based data on its effectiveness and safety. METHODS: We performed a retrospective chart review of patients who received mepolizumab for asthma and compared characteristics from 6 months prior to starting mepolizumab to 6 months after starting. Characteristics analyzed included demographics, history, asthma severity and eosinophil counts. RESULTS: We recruited twenty-four patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Herpes zoster has been reported post approval [136]. Cases of Herpes zoster have also been reported with mepolizumab, including during the initial clinical trials and post approval [137,138]. Patients with known helminth infections were excluded from participation in registration clinical trials for benralizumab, mepolizumab, and reslizumab, and such infections are uncommon in countries where IL-5-targeted therapies have generally been trialed.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes zoster has been reported post approval [136]. Cases of Herpes zoster have also been reported with mepolizumab, including during the initial clinical trials and post approval [137,138]. Patients with known helminth infections were excluded from participation in registration clinical trials for benralizumab, mepolizumab, and reslizumab, and such infections are uncommon in countries where IL-5-targeted therapies have generally been trialed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that monoclonal antibodies targeting type 2 inflammation are beneficial in treating symptoms in CRS and reducing polyp size in patients with CRSwNP. [26][27][28][29][30] Dupilumab recently showed a reduction in polyp size, sinus opacification, and severity of symptoms in patients with inadequately controlled CRSwNP in phase III trials, and this has led to a recent US Food and Drug Administration indication as an add-on maintenance therapy in these patients. 30 However, the question as to whether biologic agents treating type 2 inflammation would have an effect on reducing exacerbation frequency or antibiotic and/or systemic corticosteroid use still remains.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning, that although there is no evidence of increased risk of opportunistic infections in asthmatic patients receiving biologics, cases of herpes zoster have been reported in patients treated with mepolizumab, 31,32 and benralizumab 33,34 indicating that anti‐IL‐5/anti‐IL‐5R treatment might increase the risk of shingles and revealing a possible need of switching to a different class (when possible) when this kind of infection occurs. Furthermore, although considerations were reported regarding the long‐term eosinophil depletion and the incidence of opportunistic infections, neither benralizumab nor reslizumab has been proven to increase this risk 35,36 .…”
Section: When Should Switching Been Considered?mentioning
confidence: 99%
“…It is worth mentioning, that although there is no evidence of increased risk of opportunistic infections in asthmatic patients receiving biologics, cases of herpes zoster have been reported in patients treated with mepolizumab, 31,32 and benralizumab 33,34 indicating that anti-IL-5/anti-IL-5R treatment might increase the risk of shingles and revealing a possible need of switching to a different class (when possible) when this kind of infection occurs.…”
Section: When S Hould Switching B Een Cons Idered?mentioning
confidence: 99%